A distribuição do filme nacional: considerações acerca de cinco filmes lançados em 2005 - Silva, Hadija Chalupe da (2009)
his dissertation sets out a comparative analysis of the strategies for insertion of the national movies in Brazilian market, examining the distribution methods of a film that cares a wide-release campaign1, medium films and low films2 ,which usually does not cover the production costs and investments. Therefore, this research contributes in a way to establish the Brazilian film commercialization scenery nowadays. The following productions all released in 2005 were chosen as examination objects for the purpose: Dois Filhos de Francisco (Two Sons of Francisco), from the director Breno Silveira; Cabra Cega, directed by Toni Venturi; Casa de Areia (The House of Sand) directed by Andrucha Waddington; Cidade Baixa (Lower City), directed by Sérgio Machado; e Cinema, Aspirinas e Urubus (Movies, Aspirins and Vultures), from the director Marcelo Gomes.